Factors Affecting Knowledge Management and Its Effect on Organizational Performance with Human Capital As A Mediator - Fadil Abdullah Lating; Dwi Nita Aryani (Green Publisher Indonesia, 2024)
In the era of globalization and increasingly fierce competition, companies need to be able to manage and utilize the knowledge possessed by their employees effectively, This type of research is descriptive quantitative. the population is employees with the staff/supervisor level of Korean Multinational Company in Indonesia, totaling 80 employ-ees. While the sample taken in this study were employees with the staff/supervisor level at Multinational companies from South Korea in Indonesia, namely 80 people. The sam-pling method in this study was nonprobability sampling, with the data collection instrument using a questionnaire. Data analysis in this study used the Partial Least Square (PLS) ap-proach, namely Structural Equation Modeling (SEM). With the results that leadership has no influence on knowledge management, leadership has an influence on organizational performance, organizational culture has an influence on knowledge management, organi-zational culture has an influence on organizational performance, organizational structure has an influence on knowledge management, organizational structure has an influence on organizational performance, knowledge management has no influence on organizational performance, knowledge management has an influence on human capital, Human Capital is not able to mediate the influence of knowledge management on organizational perfor-mance. So it is recommended for companies to be able to provide more training or insight related to the importance of the role of knowledge management, so that employees can truly apply and implement knowledge management in their daily work.